New taxa of the Lygistorrhinidae (Diptera: Sciaroidea) and their implications for a phylogenetic analysis of the family - Hippa, Heikki; Mattsson, Ingegerd; Vilkamaa, Pekka (Zootaxa, 2005)
New Oriental taxa of the Lygistorrhinidae - Blagorrhina gen. n., with B. blagoderovi sp. n. and B. brevicornis sp. n.; Gracilorrhina gracilis gen. n., sp. n.; and Labellorrhina gen. n., with L. grimaldii sp. n. and L. quantula sp. n. are described, and two undescribed species, known only from females, are characterized. Based on this new material, the family is redefined. The phylogeneticrelationships among the taxa of Lygistorrhinidae were studied by parsimony analysis using 43 morphological characters from the adults of 25 ingroup and one outgroup species. The cladistic analysis produced 14 most parsimonious cladograms. The solution obtained suggests unambiguously the following phylogeny: Palaeognoriste Meunier and “Lygistorrhina” asiatica Senior-White are successively sister groups of the rest of the Lygistorrhinidae; there is a clade Labellorrhina + (Gracil- orrhina + (Blagorrhina + ((Seguyola Matile + (Loyugesa Grimaldi & Blagoderov + Matileola Papp))))) with a monophyletic Lygistorrhina Skuse – Probolaeus Williston lineage as sister group. The phylogeny among the latter group remains largely unresolved.